A technique for overlapping computation and communication for block recursive algorithms - GUPTA, S. K. S.; HUANG, C.-H.; SADAYAPPAN, P.; JOHNSON, R. W. (Concurrency (Chichester, England.), 1998)
This paper presents a design methodology for developing efficient distributed‐memory parallel programs for block recursive algorithms such as the fast Fourier transform (FFT) and bitonic sort. This design methodology is specifically suited for most modern supercomputers having a distributed‐memory architecture with a circuit‐switched or wormhole routed mesh or a hypercube interconnection network. A mathematical framework based on the tensor product and other matrix operations is used for representing algorithms. Communication‐efficient implementations with effectively overlapped computation and communication are achieved by manipulating the mathematical representation using the tensor product algebra. Performance results for FFT programs on the Intel Paragon are presented. © 1998 John Wiley & Sons, Ltd.